Ti3+ self-doped Li4Ti5O12 nanosheets as anode materials for high performance lithium ion batteries. Issue 30 (2nd March 2015) - Nie, Sen; Li, Chunsong; Peng, Hongrui; Li, Guicun; Chen, Kezheng
Abstract : Ti 3+ self-doped Li4 Ti5 O12 (S-LTO) nanosheets exhibit high specific capacity, excellent rate performance and outstanding cycling stability. Abstract : Ti 3+ self-doped Li4 Ti5 O12 (S-LTO) nanosheets have been synthesized via a facile solvothermal approach combined with hydrogenation treatment. The thickness and lateral dimension of Li4 Ti5 O12 nanosheets are 10–20 nm and 100–400 nm, respectively. The Ti 3+ species and/or oxygen vacancies are well introduced into the crystal structures of Li4 Ti5 O12 after hydrogen reduction, resulting into an enhancement in the electronic conductivity and the modified surface electrochemical activity. When evaluated for lithium storage capacity, the S-LTO nanosheets exhibit enhanced electrochemical energy storage performances compared to the pristine Li4 Ti5 O12 (P-LTO) nanosheets, including high capacity (165.6 mA h g −1 at 0.5 C), excellent rate capability (119.6 mA h g −1 at 20 C), and good cyclic stability (95.3% capacity retention after 100 cycles at 10 C). The improvement of lithium storage performances is ascribed to the increased electronic conductivity and the shortened lithium ion diffusion paths arising from the introduction of Ti 3+ species and the ultrathin thickness of S-LTO.